Enhanced angiotensin-converting enzyme inhibition and antioxidant activities through synergistic green tea and black rice extracts - Worrapob Chaisan; Nuttinee Salee; Peeraporn Pakakaew; Niramon Utama-ang (Food Chemistry Advances)
The study investigated the synergistic effects of green tea extract (GTE) and black rice extract (BRE) on total phenolic content, flavonoid content, antioxidant activities and angiotensin-converting enzyme (ACE) inhibition. The influence of GTE concentrations (14.64–85.36 % w/w) and pH levels (3.59–6.41) was analyzed by regression and response surface methodology. Optimized conditions of synergistic effect (85.36 % w/w GTE and 14.64 % of BRE at pH 6.0) yielded the highest antioxidant activities (DPPH IC50 = 0.112±0.015 mg/mL, ABTS = 89.14±1.58 mmol TE/100 g, FRAP = 373.66±3.42 mmol Fe2+/100 g), the highest total phenolic (120.98±1.60 mmol GAE/100 g), flavonoid contents (15.28±1.07 mmol QE/100 g) and ACE inhibitory activity (IC50 = 6.125±0.106 μg/mL). Therefore, this condition was selected to produce the combined extract for determining the combination index (CI). The CI was 0.349±0.075 for DPPH and 0.505±0.019 for ACE inhibition, indicating confirmation of a synergistic effect. These findings suggest that the combined extract could serve as a valuable functional ingredient, enhancing access to bioactive-rich resources for nutritionally supportive and sustainable diets. With potential applications in food systems and healthcare, this agro-ingredient may contribute to improved access to resources for blood pressure management and non-communicable disease (NCDs) prevention, aligning with broader goals in nutrition and health equity.